Pendampingan Budidaya Alpukat Menuju Santripreneur GO GREEN di PONPES Irsyaduth Tholabah Padangan - Ririn Fauziyah; Eko Arief Cahyono; Muhammad Zaenal Abidin; Burhanatut Dyana (STMIK Royal, 2026)
Abstract: The problem faced by Ponpes Irsyaduth Tholabah Padangan is the limited knowledge and skills of the students in efficient and environmentally friendly avocado cultivation. Many students are not familiar with sustainable farming methods, so they still rely on traditional ways that are less efficient and potentially harmful to the environment. In addition, the lack of understanding of agricultural business management and digital marketing is also another problem in optimizing agricultural yields. This activity aims to increase the entrepreneurial capacity of the students through avocado cultivation as an environmentally friendly and sustainable economic potential. This program is implemented at Ponpes Irsyaduth Tholabah, Padangan, Bojonegoro Regency, with a participatory and educational approach. The main focus of the mentoring includes the transfer of knowledge about avocado cultivation techniques, agribusiness management, and the strengthening of entrepreneurial spirit based on Islamic values. Through a series of training and field practice, the students not only gain technical skills in planting avocados, but are also able to design business models that support the go green principle. The steps of activity implementation are as follows: a) Activity location survey, b) Pre-Test, c) Avocado Cultivation and Digital Marketing Training, d) Post-Test. The results of the activities show an increase in students' understanding of sustainable farming concepts and the emergence of small business initiatives based on agricultural products. This program is expected to become the embryo for producing a generation of students who are economically independent and concerned about environmental sustainability. Keywords: avocado farming; go green; santripreneur; sustainable economy Abstrak: Permasalahan yang dihadapi oleh Ponpes Irsyaduth Tholabah Padangan adalah terbatasnya pengetahuan dan keterampilan santri dalam budidaya alpukat yang efisien dan ramah lingkungan. Banyak santri yang belum terbiasa dengan metode pertanian yang berkelanjutan, sehingga masih mengandalkan cara-cara tradisional yang kurang efisien dan berpotensi merusak lingkungan. Selain itu, kurangnya pemahaman tentang manajemen usaha pertanian dan pemasaran digital juga menjadi permasalahan lain dalam mengoptimalkan hasil pertanian. Kegiatan ini bertujuan untuk meningkatkan kapasitas kewirausahaan santri melalui budidaya alpukat sebagai potensi ekonomi yang ramah lingkungan dan berkelanjutan. Program ini dilaksanakan di Pondok Pesantren Irsyaduth Tholabah, Padangan, Kabupaten Bojonegoro, dengan pendekatan partisipatif dan edukatif. Fokus utama pendampingan mencakup transfer pengetahuan tentang teknik budidaya alpukat, pengelolaan agribisnis, serta penguatan semangat kewirausahaan berbasis nilai-nilai keislaman. Melalui serangkaian pelatihan dan praktek lapangan, santri tidak hanya mendapatkan keterampilan teknis dalam menanam alpukat, tetapi juga mampu merancang model usaha yang mendukung prinsip go green. Langkah-langkah pelaksanaan kegiatan sebagai berikut: a) Survey lokasi Kegiatan, b) Pre-Test, c) Pelatihan Budidaya Alpukat dan Pemasaran Digital, d) Post-Test. Hasil kegiatan menunjukkan adanya peningkatan pemahaman santri terhadap konsep pertanian berkelanjutan dan munculnya inisiatif usaha kecil berbasis hasil pertanian. Program ini diharapkan menjadi embrio lahirnya generasi santri yang mandiri secara ekonomi dan peduli terhadap kelestarian lingkungan. Kata kunci: budidaya alpukat; ekonomi berkelanjutan; go green; santripreneur